Analysis of Land Use Land Cover Dynamics and Driving Factors in Desa'a Forest in Northern Ethiopia. (February 2021) - Hishe, Hadgu; Giday, Kidane; Van Orshoven, Jos; Muys, Bart; Taheri, Fatemeh; Azadi, Hossein; Feng, Lei; Zamani, Omid; Mirzaei, Mohsen; Witlox, Frank
Highlights: This study aimed to investigate land use and cover change (LUCC) and its deriving factors in Desa'a forest This study applied spatial and radiometric corrections to make the multi-temporal images comparable The results showed that the classification has been achieved with a high accuracy of 91% Illegal logging and high dependency of the community on the forest were recognized as the main drivers of LUCC Of the total area, 48.000 ha of the forests in 1970s have now disappeared, largely replaced by farmland and bare land Abstract: Understanding the dynamic of land use/land cover (LULC) can assist relevant authorities in implementing them along with management options for natural forests like Desa'a forest in Northern Ethiopia. It is worth mentioning that no comprehensive study has been done so far on the overall change of LULC within the surrounding of Desa'a forest areas. This study aimed at analyzing the LULC changes and driving factors in Desa'a forest through Landsat images (i.e., 1973 (MSS), 1986 (TM), and 2015 (OLI)) and maximum likelihood supervised classification. Post classification pixel to pixel comparison was also performed to detect changes from year to year. Finally, focus group discussions were made to identify the LULC change drivers and support the computer-based classifications accuracy. Results demonstrated that both dense (54.11%) and open forest (28.48%) in 1973 covered almost 83% of the total forest area while only 17% was covered by grasslands (10%), farmland (3%), and bare land (4%). This is despite the fact that woody vegetation covered only 39% of the total forest reserve in 2015. During the study period, almost 54, 000 ha of grasslands and open and dense forests have been converted to either bare land or farmland, of which 48, 163 ha were previously open dense forests. Continuing with such a trend will lead to more severe deforestation and it is necessary to identify and modify the driving variables in Desa'a forest. The results also showed that fire, agricultural expansion, grazing and browsing effect, drought, extraction of wood, and lack of government attention are the major deforestation driver in Desa'a forest. The results of this study can provide a practical perspective for land use planners to manage LULC changes, reduce greenhouse gases, and enhance the biodiversity conservation in the region. In addition, the findings of the current study could provide a perfect source for calculations and choosing the best policy-making decisions to protect and manage plans for Desa'a forest.